ChemInform Abstract: Chemical Bonding in RFe6Ge4 (R: Li, Sc, Zr) and LuTi6Sn4 with Rhombohedral LiFe6Ge4 Type Structure. Issue 12 (March 2015) - Matar, Samir F.; Fickenscher, Thomas; Gerke, Birgit; Niehaus, Oliver; Rodewald, Ute Ch; Alam, Adel F. Al; Ouaini, Naim; Poettgen, Rainer
Abstract Polycrystalline ScFe6Ge4 is prepared by arc melting of stoichiometric amounts of the elements from which single crystals are grown by annealing (muffle furnace, 970 K, 3 weeks).